2022
DOI: 10.1002/mnfr.202200112
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbes Are Associated with the Vascular Beneficial Effects of Dietary Strawberry on Metabolic Syndrome‐Induced Vascular Inflammation

Abstract: Scope: Metabolic syndrome (MetS) alters the gut microbial ecology and increases the risk of cardiovascular disease. This study investigates whether strawberry consumption reduces vascular complications in an animal model of MetS and identifies whether this effect is associated with changes in the composition of gut microbes. Methods and results: Seven-week-old male mice consume diets with 10% (C) or 60% kcal from fat (high-fat diet fed mice; HF) for 12 weeks and subgroups are fed a 2.35% freeze-dried strawberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Evidence indicates a strong link between diet, gut microbes, and cardiovascular health. 9,37 Indeed, the effect of diet-derived microbial metabolites such as short-chain fatty acids and TMAO on vasculature is well-documented. 1,9 Human studies showed that circulating TMAO and its precursors are associated with an increased risk of cardiovascular disease, atherosclerotic burden, and death due to arterial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates a strong link between diet, gut microbes, and cardiovascular health. 9,37 Indeed, the effect of diet-derived microbial metabolites such as short-chain fatty acids and TMAO on vasculature is well-documented. 1,9 Human studies showed that circulating TMAO and its precursors are associated with an increased risk of cardiovascular disease, atherosclerotic burden, and death due to arterial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose concentrations were measured at 0, 15, 30, 60, and 120 min following glucose administration. [39,40] An intraperitoneal insulin tolerance test (IPITT) was conducted after a 4-h fast following insulin injection (0.75 units kg −1 of body weight). Blood glucose concentrations were measured 0, 15, 30, 60, and 120 min after insulin injection.…”
Section: Methodsmentioning
confidence: 99%
“…Blood glucose concentrations were measured 0, 15, 30, 60, and 120 min after insulin injection. [39,40] Using the LF50 body composition mice analyzer (Minispec; Bruker, Germany), total body fat and lean body mass was assessed by TD-NMR. [39,40] After the 12-week treatment period, mice were anesthetized with 2%-5% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations